The asymmetric elastic wavefields in a model comprising a liquid layer overlying an anisotropic solid seabed due to an arbitrary source within the solid. (January 2017) - Bagheri, Amirhossein; Khojasteh, Ali; Rahimian, Mohammad; Greenhalgh, Stewart; Attarnejad, Reza
Highlights: The elastodynamic response of an ocean model with an anisotropic seabed is studied. The source can act at any point within the seabed and may have different shapes. The effect of source location, frequency, and presence of the liquid are examined. Closed-form solutions for wavefield components are valid at any point in the model. Contribution by any number of possible acoustic modes are included in the results. Abstract: The asymmetric three-dimensional radiation pattern and resultant elastodynamic response of stress waves in a model comprising a compressible water column overlying a transversely isotropic seabed in which a time-harmonic source acts is theoretically investigated. The use of potential functions, the Hankel transform, and a Fourier series expansion are adopted to deal with the equations of motion for both media. Closed-form integral expressions are developed for the potentials and the stress/displacement components. The expressions and introduced procedure are sufficiently flexible to incorporate various types of source loads. To evaluate the field quantities, the residue method and a robust integration scheme are utilized to handle the poles and branch points within the integrand. Any possible number of dispersive propagation modes are taken into account in the integral evaluation. The deduced velocity dispersion curves depict the characteristics of the various modes. They also indicate the existing singular points (poles) for a specific dimensionless frequency and the surface wave type associated with each pole. Numerical results are presented for the hydrodynamic pressure and displacement in the liquid layer and stress and displacement components in the solid seabed due to distributed and concentrated source excitations. The formulation and the numerical scheme are valid for calculating the wavefield anywhere within the model including both far- and near-field effects. The sensitivity of the results to different parameters is also analyzed. Both analytical and numerical comparisons with existing solutions for simpler cases are made to confirm the validity of the results. The results are especially useful in seismic hazard assessment of submarine earthquakes, landslides, and tsunamis. They can also be extended to deal with the fluid-solid-structure interaction problems.